2005
DOI: 10.1007/s00167-005-0667-0
|View full text |Cite
|
Sign up to set email alerts
|

Native femoral sulcus as a guide for the position of the femoral component in primary total knee arthroplasty

Abstract: A prospective randomized study was conducted to evaluate the effects of using the native femoral sulcus as a guide for the positioning of the femoral component in primary total knee arthroplasty (TKA), especially for patellar tracking. Between 2000 and 2002, 420 cases of primary TKA were collected. All the TKAs were performed with the same approach. The cases were randomly separated into two groups. In group 1 (consisting of 202 knees), the femoral insertion of the posterior cruciate ligament and the midline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The lateral location of the sulcus relative to the midline of the intact femoral condyles has been reported previously [5][6][7][8]. Eckhoff et al found the sulcus to lie about 5 mm lateral to the midline, with the midline being defined as the perpendicular bisector of a baseline connecting the most posterior points of the medial and lateral femoral condyles [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lateral location of the sulcus relative to the midline of the intact femoral condyles has been reported previously [5][6][7][8]. Eckhoff et al found the sulcus to lie about 5 mm lateral to the midline, with the midline being defined as the perpendicular bisector of a baseline connecting the most posterior points of the medial and lateral femoral condyles [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…At surgery, the line marking the native femoral sulcus is identical to Whiteside's line or the anteroposterior axis of the distal femur [2,[4][5][6]14]. The marked line was used to determine the rotational alignment of the femoral component, by cutting the anterior aspect of the femoral condyles perpendicular to it [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the operative technique, prosthetic design, axial malalignment and malrotation as well as poor patellar tracking contributed to the patellofemoral complications [ 4 – 7 ]. Besides, femoral component designs and position were also reported as the main causes of poor patellar tracking in TKA [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, previous studies have reported that native femoral sulcus could be used as a guide for the femoral component position in TKA [ 8 , 18 ]. However, it was not known yet whether trochlear groove was shifting with line of force in severe osteoarthritic knee, and whether the positioning of the femoral component using trochlear groove as reference contributed to the reconstruction of patellar tracking in patients with severe knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%